Prevention of halophilic microbial damage on brine cured hides by extremely halophilic halocin producer strains - (:unkn) unknown (SOC LEATHER TECHNOL CHEMISTS, 2004)
Tuz Lake and its salterns; Kayacik, Kaldirim and Tuzkoy Salt Mine in Central Anatolia are the major salt sources of Turkey. Crude salt extracted from these sources is commonly used in hide preservation. Proteolytic activity of extremely halophilic microorganisms, present in the salt used for hide preservation, can digest the grain surface of hides. Many bactericides have therefore, been used in the leather industry to prevent damage by halophiles. However, natural proteinaceous antimicrobial substances such as halocins which are produced by halophilic archaea may be an effective and pollution free alternative to inhibit the proteolytic halophilic archaea in brine solutions. The above reason prompted us to conduct a microbial survey of the salt and brine samples collected from different salt sources in Turkey. A total of 56 extremely halophilic strains were isolated from these salt sources. It was found that 67% of the Tuzkoy Salt Mine and Kaldirim Saltern strains had gelatinase activity. Kayacik Saltern had the highest number of gelatinase positive strains (71%), while the Tuz Lake had the lowest number of gelatinase positive strains (63%). Seven out of 19 Tuz Lake strains, 16 out of 18 Kaldirim Saltern strains, 2 out of 7 Kayacik Saltern strains and 10 out of 12 Tuzkoy Salt Mine strains produced halocins effective against each other. The most potent halocin producers were found in Kaldirim Saltern and the Tuzkoy Salt Mine. All the cells of halocin producers were Gram negative, motile and most of them were pleomorphic. The susceptibilities to different antibiotics of the halocin producer strains were examined and antibiotic test results indicated that these strains were of the family Halobacteriaceae. Although many gelatinase negative halocin producers were isolated from different salt sources, the KYS1 strain was found to be the most effective strain in inhibiting all gelatinase positive strains of Kayacik Saltern and some of the other gelatinase positive strains which could not be inhibited by the Tuz Lake and Tuzkoy Salt Mine strains. It is suggested that gelatinase negative halocin producers or their halocin extracts may be used in preventing the halobacterial deterioration that can occur during brine curing of hides.
Keywords: BACTERIA; QUALITY; ARCHAEA